Study on Knowledge about Arsenic Contamination in Drinking Water among the People Living in Selected Villages of Bangladesh (Journal of Shaheed Suhrawardy Medical College, 2017)
Background: Excessive amounts of arsenic (As) in the groundwater in Bangladesh and neighbouring countries are also a major public health problem.Objective: The purpose of the present study was to find out the knowledge of arsenic contamination in drinking water and health hazards due to chronic arsenic toxicity among the people living in selected villages of Bangladesh.Methodology: This cross sectional descriptive type of study was conducted purposively among the people of the selected two villages of Bhanga Upazilla of Faridpur district from January 2007 to June 2007. All the relevant socio-demographic characteristics and data were collected by face to face interview.Results: A total number of 360 people were recruited. It was found that 273(85.3%) of the respondents family member used tube well water for drinking purpose of the respondents, 317(99.1%) persons heard of arsenic contamination in drinking water. About 284 (88.8%) respondents had the correct knowledge about identifying color of arsenic contaminated and arsenic free tube well. It was found that l76(55.5%) people knew the correct answer about the duration of use of arsenic contaminated water to causes chronic arsenic toxicity. It also revealed that 107(33.4%) respondents did not know about sign of chronic arsenic toxicity.Conclusion: Excellent knowledge on arsenic contamination in drinking water and health hazards due to chronic arsenic toxicity is found among the people living in selected villages of Bangladesh.J Shaheed Suhrawardy Med Coll, 2014; 6(2):57-59